Shoot and Root Growth and Yield of Eggplant Cultivars as Affected by Wilt Disease - Akhter Hossain2, Md. Ashrafur Rahman1*, Farjana Ali2, K.M (Journal of Experimental Sciences, 2011)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> An experiment was conducted in the Field of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh to screen out the resistant cultivars of eggplant against wilt disease. Eight cultivars viz. Nayantara, Singhnath, Dhundul, Kazla, Marich Begun Luffa, Kata Begun and Uttara were used as treatments. The highest shoot height was recorded in the cultivar Kata Begun and the lowest shoot height was recorded in the cultivar Singhnath. The highest gall number was recorded in the cultivar Luffa and the lowest gall number was recorded in the cultivar Kata Begun. The highest yield per hectare (29.84 t/ha) was recorded in the cultivar Nayantara and the lowest yield (10.50 t/ha) was recorded in the cultivar Dhundhul. Among the cultivars Kata Begun graded as resistant for both Bacterial, Fungal and Nemic wilt.